MANUSIA MENURUT PLATO DALAM PERSPEKTIF VEDĀNTA - Ayu Veronika Somawati; Yunitha Asri Diantary Ni Made (Sanjiwani: Jurnal Filsafat, 2020)
Humans are God's creatures called the most perfect creatures. This is because humans have the provision of life that is not possessed by other creatures, namely the ability to think and reason. This ability, makes humans always try to achieve a more established life physically and spiritually, both by making innovations to facilitate each of his life activities or by exploring the values ​​contained in his life in order to better interpret life and find the essence of life itself. One of the things that has always been a topic of discussion in order to explore the values ​​contained in human life is to look for the meaning of what and who a person is as a whole and who human really is. By interpreting this, it is hoped that humans themselves can easily make themselves practical decisions in carrying out life, taking meaning from every event that occurs in life and determining the direction and purpose of life. Various kinds of views about humans expressed by philosophers, both eastern philosophers and western philosophers. One of them is Plato. Plato was one of the western philosophers who were students of Socrates. Plato was born in 427 (BC) to the Athenian family. After the death of his teacher, Plato together with his friends who are passionate to continue the ideals of their teachers. In his view of humans, Plato's thoughts have a common thread with the view of Hindu Philosophy especially Vedāntaboth about the true reality of humans and the view of good human beings. The method used in this research is a descriptive method that will systematically describe Plato's thoughts about humans that are related to the view of Hindu Philosophy Vedānta.